Design of silicon Mach-Zehnder modulators employing deep neural networks - de Paula, Rômulo [UNESP]; Bustamante, Yesica R.R.; Sutili, Tiago; Figueiredo, Rafael C.; Abbade, Marcelo Luis F. [UNESP]; Aldaya, Ivan [UNESP] (My University, 2022)
We present an efficient o ptimization m ethod f or t he d esign o f silicon-on-insulator integrated Mach-Zehnder modulators based on a deep neural network that is capable of predicting the main figures of merit from the modulator design variables.